The Prevalence and Genotype Distribution of Human Papillomaviruses Among Men in Henan Province of China - Wang, Huiling; Zhao, Jing; Liu, Xiaoli; Yan, Wenjuan; Li, Gang; Yuan, Youhua (Frontiers in Medicine, 2021)
Background: This paper aimed to assess the prevalence of human papillomavirus (HPV) infection and the associations of sociodemographic and behavioral characteristics with HPV in unvaccinated men in the Henan Province before the mass administration of the HPV vaccine through a baseline survey. Methods: Between 2015 and 2020, 3690 men were tested for the HPV genotype at the Henan Provincial People’s Hospital. The HPV genotype was detected by a polymerase chain reaction (PCR)-based hybridization gene chip assay. Results: The overall HPV infection rate was 29.97%; The most prevalent genotypes were HPV 6 (21.76%), 11 (12.68%), 16 (8.94%), 58 (5.37%), 18 (3.41%), 84 (3.25%), 61 (3.09%), and 81 (3.09%). Low-risk HPV (LR-HPV) infection (24.91%) and single infection (17.78%) were the most prevalent forms. Age-specific HPV distribution was presented as a bimodal curve; the youngest age group (≤25 years) had the highest HPV infection rate (36.03%), followed by the 36–40-year-old group (33.68％). Men with Junior high school or above were more likely to have Pure-LR HPV infection. Unmarried status and smoking increased single and LR-HPV infection. Multiple lifetime sex partners and not using a condom were more likely to cause LR-HPV infection. Conclusions: The data on the prevalence and HPV infection type distribution in men in the Henan Province could serve as a valuable reference to guide nationwide screening. We provide a time-based estimate of the maximum impact of the HPV vaccine and critical reference measurements important for assessing the clinical benefits of HPV vaccination and the increase in non-vaccine HPV types.